2015
DOI: 10.1111/ijun.12080
|View full text |Cite
|
Sign up to set email alerts
|

Encrustations of the urinary catheter and prevention strategies: a literature review

Abstract: Patients with an indwelling urinary catheter are at risk of developing urinary tract infection: for each day of the catheter remaining in situ, there is an increasing risk from 3% to 7% for infection to appear. One of the main complications of catheterization is the onset of encrustations, frequently resulting in obstruction of the catheter. Aim of this study is to describe the problem of indwelling urinary catheter encrustation and prevention strategies. A narrative review of the literature was conducted. Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Of the various types of Foley catheters available, silicone catheters have been shown to display optimal performance in preventing encrustation because of Revalidation Prepare for revalidation: read this CPD article, answer the quiz and write a reflective account. For more information, go to rcni.com/ revalidation nursingstandard.com volume 34 number 9 / September 2019 / 63 | PEER-REVIEWED | their relatively large lumen size and since they can remain in situ for longer than other types of catheter (Marcone Marchitti et al 2015a). The EAUN (2012) guidelines recommend a 100% silicone catheter for patients who have a latex allergy and for those who experience frequent catheter blockages.…”
Section: Optimal Type Of Catheter To Prevent Blockagesmentioning
confidence: 99%
“…Of the various types of Foley catheters available, silicone catheters have been shown to display optimal performance in preventing encrustation because of Revalidation Prepare for revalidation: read this CPD article, answer the quiz and write a reflective account. For more information, go to rcni.com/ revalidation nursingstandard.com volume 34 number 9 / September 2019 / 63 | PEER-REVIEWED | their relatively large lumen size and since they can remain in situ for longer than other types of catheter (Marcone Marchitti et al 2015a). The EAUN (2012) guidelines recommend a 100% silicone catheter for patients who have a latex allergy and for those who experience frequent catheter blockages.…”
Section: Optimal Type Of Catheter To Prevent Blockagesmentioning
confidence: 99%
“…The literature suggests that there are manifold strategies concerning the prevention of IUC encrustations; some of them need a pharmacological intervention (e.g. antibiotics, silver nitrate, urease inhibitors, Ibicella lutea , biocide triclosan, bacteriophage therapy, washouts) (Kennedy et al , ; Getliffe, ; Morris and Stickler, ; Choong et al , ; Schierholz et al , ; Williams and Stickler, ; Carson et al , ; Sosa and Zunino, ; Marcone Marchitti et al , ). In contrast other studies, have showed how the formation of encrustations can be reduced without using pharmacological treatments (e.g.…”
Section: Background For the Studymentioning
confidence: 99%